Extreme killing: understanding serial and mass murder - Fox, James Alan (Sage Publications, 2012)
Filled with contemporary and classic case studies, this fully updated Second Edition illustrates the many violent expressions of power, revenge, terror, greed, and loyalty. Throughout the book, renowned experts James Alan Fox and Jack Levin examine the theories of criminal behavior and apply them to a multitude of well-known and lesser-known multiple homicide cases from around the world. The book shows readers the commonalities and variations among multiple murders; addresses the characteristics of both killers and their victims; and, in the concluding chapter, discusses the special concerns of multiple murder victims and their survivors. --